Characterization of Lignin Biosynthesis Encoding Gene, SiCOMT, from Nine Indonesian Foxtail Millet (Setaria italica (L.) P. Beauv.) Genotypes - Rizqullah, Ramadaniarto; Saenal, Nirwanti; Pahlevi, M Reza; Suwarno, Willy Bayuardi; Tsugama, Daisuke; Ardie, Sintho Wahyuning (HAYATI Journal of Biosciences, 2026)
Caffeic acid O-methyltransferase (COMT) is an essential enzyme that catalyzes the biosynthesis of lignin monomer units. Foxtail millet (Setaria italica) possesses three COMT-encoding genes. However, only SiCOMT1 and SiCOMT2 are considered expressed. This study investigates the characteristics of the two COMT-encoding genes across nine Indonesian foxtail millet genotypes. Phylogenetic analysis revealed that SiCOMT1 is closely related to N-methyltransferase genes, which are not involved in the lignin biosynthesis pathway. Meanwhile, SiCOMT2 is closely related to O-methyltransferase genes involved in lignin biosynthesis. SiCOMT2 from nine Indonesian foxtail millet genotypes exhibits 15 synonymous and three non-synonymous SNPs. SiCOMT2 amino acid showed Ala67Thr and Pro72Ala variations within the methyltransferase dimerization domain, and Glu146Asp within the O-methyltransferase domain. Among these, the Pro72Ala substitution is predicted to reduce the structural stability of the encoded protein. These findings suggest that SiCOMT2 may serve as a promising target for future genetic research and crop improvement strategies aimed at enhancing biomass quality by modifying lignin content and composition.